O imaginário da cidade no pacto socioambiental de um plano diretor municipal : o planejamento urbano e a lei em Vila Velha, ES-1948-2008 - Chalhub Júnior, José Antonio (2009)
The research aims to build an environmental pact as a precondition for human coexistence in urban society, based on political sciences and its key thinkers. Still, in the constitution of a city’s imaginary, through the identification of elements of histor